Rendimiento académico en estudiantes de odontología que trabajaron durante la virtualidad en pandemia COVID-19 (2023)
The COVID-19 pandemic affected education, forcing students to modify their methodologies to adapt to new academic conditions. In this way, an effort was made to understand the experiences of students who worked and studied during this period.